Mapping Transnational Islamic Education Networks in Southeast Asia: A Qualitative Social Network Analysis Approach - Ruslaini; Fajri Ismail; Indah Wigati; Yuniar (Sustainable, 2026)
This study examines the structure and dynamics of transnational Islamic education networks in Southeast Asia through a qualitative literature review and a Social Network Analysis (SNA) perspective. Synthesizing 45 relevant peer-reviewed articles drawn from scholarly works published between 2020 and 2025, the research explores how traditional institutions such as pesantren and madrasah interact with modern educational systems and global networks. The findings reveal that Islamic education in the region is characterized by a hybrid structure, integrating localized religious traditions with transnational knowledge flows, particularly through connections with the Middle East and other Muslim-majority regions. Key actors, including ulama, educational institutions, and state agencies, play crucial roles in facilitating collaboration, curriculum transformation, and knowledge dissemination across borders. Furthermore, the study highlights the impact of globalization and digitalization in expanding access to Islamic knowledge while simultaneously introducing challenges related to institutional autonomy and resource disparities. By mapping these relationships conceptually, this research contributes to a deeper understanding of how Islamic education networks evolve within a globalized context. It also provides insights into policy development and institutional strategies to strengthen collaboration, promote moderation, and enhance the global competitiveness of Islamic education in Southeast Asia.